Deducción de gastos personales e incidencia en la recaudación del impuesto a la renta 2023, de la ciudad de Guayaquil - Arévalo Jima, Lissette Johanna (2025)
he study entitled ‘Deduction of Personal Expenses and Incidence on Income Tax Collection 2023, in the City of Guayaquil’ analyzes how tax deductions affect tax collection in Ecuador. The research starts from the premise that taxes are fundamental for the redistribution of wealth, focusing on how the deduction of personal expenses influences income tax collection. To this end, a mixed approach was used, combining quantitative and qualitative methods, which allowed for a comprehensive view of the fiscal impact of these deductions in Guayaquil during 2023. The results of this study reveal that deductions for personal expenses not only decrease total tax collection, but also improve the perceived fairness of the tax system. It was identified that higher - income taxpayers, who take advantage of deductions, face a higher tax burden in absolute terms, which reinforces the progressivity of the tax system. Furthermore, it was observed that these deductions allow adjusting the tax burden according to the real economic capacity of taxpayers, encouraging greater compliance with tax obligations. In conclusion, the deduction of personal expenses has a dual impact on revenue collection which reduces total revenue, but improves the fairness of the tax system. Finally, it is recommended that tax policies continue to promote these deductions, as they foster tax fairness and strengthen trust of citizens in tax institutions.